(untitled) (Asian Journal of Social Science Studies, 2022)
Bleak House, as Dickens’ outstanding “legal novel”, is often regarded as an important research text by many jurists and litterateurs. With the rise of the Law and Literature movement, scholars pay more attention to the interaction between the legal description in Bleak House and the law in reality. The legal elements of the novel revolve around three main cases. Firstly, through combing, it is found that the criticism of the Court of Chancery in Bleak House is more metaphorical and literal language expressed through literary devices, rather than pointing out the specific legal procedures or provisions that lead to the delay and pedantry of the Court of Chancery. As a novelist, however, Dickens was not obliged to pass judgment on specific laws. Then, we find that the way he writes is related to his life experience. Through the study of Dickens’ relationship with law and the Court of Chancery, this paper reveals the relationship between Dickens and the Court of Chancery, and shows the emotional root of the novel’s serious denial of the judicial system and the Court of Chancery. Finally, this paper deeply analyzes the realistic significance of Bleak House, expounds the influence of law on the novel, and analyzes the influence on society and the rule of law from the positive side and the negative side.